THE INFLUENCE OF PROJECT BASED LEARNING MODEL AND SOCIAL SKILLS ON THE LEARNING OUTCOMES OF PPKN CLASS V STUDENTS OF SD NEGERI 050604 BEKIUN 2020/2021 - Ester Novitalina Br Tarigan; Deny Setiawan; Daulat Saragi (Sensei International Journal of Education and Linguistic, 2021)
This research is motivated by the purpose of education to obtain prepare individuals who have the ability and skills to be better. The purpose of this study were (1) To determine the results of learning PPKn students who study by using a model of project based learning in comparison with the results of learning PPKn students who study by using a model direct instruction. (2) To determine the results of learning PPKn students who have the social skills of high much higher compared with the results of learning students who have the social skills low in the project based learning model class. (3) To determine the results of learning PPKn students who have the social skills of high much higher compared with the results of learning students who have the social skills low in the direct instruction model class. (4) This is to determine the interaction between the project based learning model and social skills on the learning outcomes of PPKn students in class V SD Negeri 050604 Bekiun. This research uses a quantitative approach. Data analysis using Tuckey-test. The results showed that (1) The Results of learning PPKn students who are taught by the model of project based learning is higher than the result of learning PPKn which is taught by using a model direct instruction, (2) The results of learning PPKn students who have the social skills of high much higher than the results learning PPKn students who have social skills low in the project based learning model class, (3) The results of learning PPKn students who have the social skills of high much higher than the results learning PPKn students who have social skills low in the direct instruction model class, (4) There is an interaction between the project based learning model and social skills on student PPKn learning outcomes.